AN ANALYSIS OF RIGHTS OFFERS: THEIR ADVANTAGES AND DRAWBACKS - Maleka Femida Cassim (Obiter, 2023)
A rights offer is a useful mechanism for raising fresh corporate finance, particularly for a listed company with a wide shareholder base. The regulation of rights offers in South African law is critically analysed in this article. This is followed by a comparative analysis of rights issues in the United Kingdom and in Australian law. The advantages and drawbacks of rights issues in practice are also discussed, with reference to recent rights offers launched by prominent JSE-listed companies.